Evaluation of Indonesia's Conventional Track Performance Based on Mechanistic Approach - Setiawan, Dian M. (International Journal of Sustainable Construction Engineering and Technology, 2022)
Most railway track dynamics models focus on the high-speed train. However, freight trains non only have strong implications for track dynamics, but also the response of conventional track subjected to the low speed of freight train models are rarely published. This paper developed a 2-Dimensional conventional railway track model based on the multipurpose finite element package Abaqus/CAE, which considers four structure layers: sleepers, ballast, sub-ballast, and subgrade subjected to three different freight train speeds (very low, low, and normal) and two different freight train axle loads (normal, 18,000 kg, and heavier, 27,000 kg). The most obvious finding to emerge from this study is that running the long-chain coal "Babaranjang" freight train with 70 km/h of operating speed and 27,000 kg of axle load is suggested to increase the hauling capacity of the Babaranjang train and at the same time to ensure the safety of its operation. Also, the present study confirms previous findings and contributes additional evidence that a train with a very low operation speed could deteriorate the conventional track structure, and it will be worsened when this type of train is operated with a higher axle load.